Basic and morphological properties of Bukit Goh bauxite - Muhammad Syamsul Imran, Zaini; Muzamir, Hasan; Ain Syaheera, Zulkafli (Penerbit UMP, 2024)
The research focuses on the basic and morphological characteristics to ensure bauxite ore reaches the International Maritime Solid Bulk Cargoes Code (IMSBC Code) standard before being exported to other countries. To analyze this characteristic of the bauxite, some laboratory tests referred to Geospec 3: Model Specification for Soil Testing had been done to identify the bauxite's basic properties: particle size distribution, moisture content and specific gravity and its morphological properties. Laboratory tests involved are hydrometer, small pycnometer, dry sieve, and scanning electron microscopy tests. About four samples were selected at Bukit Goh, Kuantan; two were from the Bukit Goh mine, and another two were from the stockpile. All studies on the characteristics of bauxite were analyzed and recorded to compare with the IMSBC Code. The analysis of the result shows that the average moisture content of the soil is 20.64%, which is above 10% from the recommended value; the value of bulk density is not in the range of 1190 kg/m3 to 1389 kg/m3, which is 2836.25 kg/m3 and the particle size distribution for fine material is greater than 30% and coarse material is less than 70%. From the SEM test, image analysis proved that there were many fine particles in bauxite samples. By the IMSBC Code, Bukit Goh bauxite cannot be categorized as group C. Hence, bauxite collected from Bukit Goh mines has yet to achieve the standard; thus, it is not suitable for export.